2023
DOI: 10.3389/fcell.2023.1147610
|View full text |Cite
|
Sign up to set email alerts
|

Divergent patterns of meiotic double strand breaks and synapsis initiation dynamics suggest an evolutionary shift in the meiosis program between American and Australian marsupials

Abstract: In eutherian mammals, hundreds of programmed DNA double-strand breaks (DSBs) are generated at the onset of meiosis. The DNA damage response is then triggered. Although the dynamics of this response is well studied in eutherian mammals, recent findings have revealed different patterns of DNA damage signaling and repair in marsupial mammals. To better characterize these differences, here we analyzed synapsis and the chromosomal distribution of meiotic DSBs markers in three different marsupial species (Thylamys e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 116 publications
(192 reference statements)
0
1
0
Order By: Relevance
“…Although our observations are compatible with synapsis elongating from the telomeres, we cannot infer the directionality of HEI10 loading. Moreover, a recent study has shown that the bouquet configuration is required for the distal bias of DSB formation and repair, possibly playing an important role in the observed reduced recombination rates at interstitial positions 66 . Future experiments in Rhynchospora will be important to identify conserved and adapted mechanisms of spatiotemporal dynamics of meiotic DSB formation and HEI10 loading.…”
Section: Discussionmentioning
confidence: 99%
“…Although our observations are compatible with synapsis elongating from the telomeres, we cannot infer the directionality of HEI10 loading. Moreover, a recent study has shown that the bouquet configuration is required for the distal bias of DSB formation and repair, possibly playing an important role in the observed reduced recombination rates at interstitial positions 66 . Future experiments in Rhynchospora will be important to identify conserved and adapted mechanisms of spatiotemporal dynamics of meiotic DSB formation and HEI10 loading.…”
Section: Discussionmentioning
confidence: 99%